Procurement of customer service delivery in telcos: A case study - Jeeva, Ananda (Edizioni Scientifiche Italiane, 2012)
This empirical paper is based on a Telecommunications company’s service delivery business process for its business customers. The researcher was a service depot manager in a prominent telecommunications company. There were numerous errors in the work orders that led to delays in telecommunication service restoration to the business community. These errors created customer dissatisfaction, loss of business to this Telco’s customers and ultimately numerous complaints to the Telecommunications Ombudsman. Data was collected by quantitative and qualitative methods from various entities along the work flow of the work order. It was found that the silo mentality was prevalent among these entities. A workshop forum of representatives from these entities was organised to discuss issues and resolve constrictions for a smoother flow of the work orders. This paper approaches this case study from a supply chain management perspective consisting of various entities with differing business objectives. The final outcome after a nine month process improvement project indicated that faulty telecommunication service could be restored within the same day. It develops a conceptual model for a service delivery framework in a complex geographical environment.